Trashepatic left gastric vein embolization in the treatment of recurrent hemorrhaging in patients with schistosomiasis previously submitted to non-derivative surgery Embolização transhepática da veia gástrica esquerda no tratamento da recidiva hemorrágica em esquistossomóticos submetidos previamente a cirurgia não derivativa - Paulo Fernandes Saad; Álvaro Razuk; Gustavo José Politzer Telles; Jong Hun Park; Fernando Pinho Esteves; Roberto Augusto Caffaro (Arquivos de Gastroenterologia, 2012)
CONTEXT: Non-derivative surgical techniques are the treatment of choice for the control of upper digestive tract hemorrhages after schistosomotic portal hypertension. However, recurrent hemorrhaging due to gastroesophagic varices is frequent. OBJECTIVE: To evaluate the outcome of treatment based on embolization of the left gastric vein to control the reoccurrence of hemorrhages caused by gastroesophagic varices in patients with schistosomiasis previously submitted to non-derivative surgery. METHODS: Rates of reoccurrence of hemorrhages and the qualitative and quantitative reduction of gastroesophagic varices in patients undergoing transhepatic embolization of the left gastric vein between December 1999 and January 2009 were studied based on medical charts and follow-up reports. RESULTS: Seven patients with a mean age of 39.3 years underwent percutaneous transhepatic embolization of the left gastric vein. The mean time between azigoportal disconnections employed in combination with splenectomy and the percutaneous approach was 8.4 ± 7.3 years, and the number of episodes of digestive hemorrhaging ranged from 1 to 7 years. No episodes of reoccurrence of hemorrhaging were found during a follow-up period which ranged from 6 months to 7 years. Endoscopic postembolization studies revealed reductions in gastroesophagic varices in all patients compared to preembolization endoscopy. CONCLUSIONS: Percutaneous transhepatic embolization of the left gastric vein in patients with schistosomiasis previously submitted to surgery resulted in a decrease in gastroesophagic varices and was shown to be effective in controlling hemorrhage reoccurrence. INTRODUÇÃO: A cirurgia por técnicas não derivativas é o tratamento de escolha para o controle da hemorragia digestiva alta secundária à hipertensão portal esquistossomótica. Contudo, a recidiva hemorrágica em decorrência das varizes gastroesofágicas é um evento frequente. O programa de erradicação endoscópica das varizes gastroesofágicas tem o objetivo de prevenir e/ou tratar a recidiva hemorrágica, porém nem todos os doentes respondem ao tratamento. OBJETIVO: Avaliar o sucesso do tratamento de embolização da veia gástrica esquerda no controle da recidiva hemorrágica por varizes gastroesofágicas nos doentes esquistossomóticos submetidos previamente a cirurgia não derivativa. MÉTODOS: Foram estudadas, por meio de dados colhidos nos prontuários médicos e dos protocolos de seguimento ambulatorial, a incidência da recidiva hemorrágica e a diminuição quantitativa e qualitativa das varizes gastroesofágicas em detrimento das varizes gastroesofágicas dos doentes encaminhados para embolização transhepática da veia gástrica esquerda no período de dezembro de 1999 até janeiro de 2009. RESULTADOS: Sete doentes com média etária de 39,3 anos foram encaminhados para embolização percutânea transhepática da veia gástrica esquerda. O tempo médio decorrido entre a DAPE e a abordagem percutânea foi de 8,4 ± 7,3 anos e o número de episódios de hemorragia digestiva variou de um a sete neste período. Nenhum episódio de ressangramento foi verificado na população do estudo durante o período de acompanhamento, que variou de 6 meses a 7 anos. Após estudo endoscópico pós-embolização, todos os doentes apresentaram diminuição das varizes gastroesofágicas em comparação à endoscopia pré-embolização. CONCLUSÃO: A embolização percutânea transepática da veia gástrica esquerda nos doentes esquistossomóticos, previamente operados, determinou a redução das varizes gastroesofágicas e foi eficiente no controle do ressangramento para a população estudada.